1986
DOI: 10.1111/j.1438-8677.1986.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Permian Palaeobotany and Palynology. Vi. Towards a Flexible System of Naming Palaeozoic Conifers

Abstract: SUMMARY A natural classification of extinct conifers requires the recognition of natural taxa. In conifers reproductive organs provide the most successful characters for delimiting natural genera and families. Based on assembled species, a genus should at least be diagnosed in terms of overall morphology of leafy shoots in combination with the organization of ovuliferous organs. In addition, detailed statements about the epidermal structure are of great practical value. However, most taxa of fossil conifer rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…With respect to the ancestry of the Majonicaceae it is here suggested that some "Walchiostrobus" species sensu Florin (Walchiostrobus has been emended to include only ovuliferous dwarf-shoots with a single fertile scale, see Visscher et al, 1986), especially those provided with many sterile scales and several fertile scales, may represent a possible ancestral form. The interpretation of Clement-Westerhof (1984) that "Walchiostrobus" dwarf-shoots do not exhibit "stalked" ovules, but bear their ovules abaxially on fertile scales has been independently confirmed by observations of Meyen (1984).…”
Section: Phylogenetic Considerationsmentioning
confidence: 97%
See 1 more Smart Citation
“…With respect to the ancestry of the Majonicaceae it is here suggested that some "Walchiostrobus" species sensu Florin (Walchiostrobus has been emended to include only ovuliferous dwarf-shoots with a single fertile scale, see Visscher et al, 1986), especially those provided with many sterile scales and several fertile scales, may represent a possible ancestral form. The interpretation of Clement-Westerhof (1984) that "Walchiostrobus" dwarf-shoots do not exhibit "stalked" ovules, but bear their ovules abaxially on fertile scales has been independently confirmed by observations of Meyen (1984).…”
Section: Phylogenetic Considerationsmentioning
confidence: 97%
“…It is here considered that Majonica, Dolomitia and Pseudovoltzia are sufficiently diagnosed in order to be regarded as natural genera (compare Visscher et al, 1986); moreover they share enough characteristics to justify classification in the same family. The only two families which may be taken into consideration are the Voltziaceae (see Pilger and Melchior, 1954) and the Ullmanniaceae (see Zimmermann, 1959).…”
Section: A New Family Of Late Permian Conifers: the Majonicaceaementioning
confidence: 99%
“…The lack of unequivocal sets of diagnostic characters, used to characterize and distinguish walchian conifer species, has prompted different approaches to solving Paleozoic conifer systematics. Hence, each approach creates different classifications with alternative morphotaxa (Table 1; Visscher et al, 1986;Mapes and Rothwell, 1991).…”
Section: Conifer Morphotaxamentioning
confidence: 99%
“…The material is characterized by isolated and fragmentary lateral branches with simple leaves that resemble many other walchian conifers around the world (Florin, 1938-45;Rothwell, 1982;Clement-Westerhof, 1987;Meyen, 1997;Rothwell et al, 1997;Kerp and Clement-Westerhof, 1991). Traditionally, fragmentary conifer remains were described as species belonging to form-genera (Florin, 1938-45;Mapes and Rothwell, 1991;Visscher et al, 1986), now known as morphotaxa (Greuter in McNeill et al, 2006). Paleozoic conifer morphotaxa lack familial affinities due to their incomplete nature and broad ranges of morphological and cuticular variation (Hernandez-Castillo et al, 2001;Hernandez-Castillo, 2005;Rothwell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation